Contributory factors to the 2003 Darfur Conflict in Sudan and African Union (AU) Intervention Strategies - Agena, James E. (2014)
There is no gainsaying the obvious that certain existential factors contributed immensely to the conflict in Darfur region of Sudan. This paper therefore is designed to interrogate into these factors with a view to establishing the extent they contributed to the escalation of the conflict. Using the theory of Relative Deprivation as a framework, the paper opines that structural inequality among the citizens and the different divides that make up the state of Sudan as well as the agitation of the perceived marginalized people of Darfur for inclusion in the political and economic gains of the country as the major causes of the conflict. The activities of the Sudanese government that used the janjaweed militias on the people instead reeling out policies for de-escalating the conflict was also a point of focus. The paper however commended the activities of the African Union especially her intervention that helped in de-escalating the conflict despite being hampered by poor funding and sophiscated military hardware. The paper however recommended for a more sincere political will on the part of the Sudanese to resolve the Darfur conflict and that the African Union should make more frantic effort aimed at providing its standby force with the necessary logistics to not only deal with the conflict in Darfur but in other troubled spot within the continent taking cognizance of the precarious nature of Africa.